Phototoxic reaction induced by pazopanib - Siriorn Udompanich (2019)
© 2018 The Author(s). Published by S. Karger AG, Basel. Multikinase inhibitors (MKIs) are a novel target therapy that offers promising long-term survival for patients with advanced-stage cancer. However, they cause a wide range of adverse reactions, skin and skin appendage being the most prevalent. Photosensitivity reactions are well-recognized effects from certain MKIs such as sunitinib and vandetanib. However, phototoxic reaction induced by pazopanib has never been reported. We present here the first case of pazopanib-induced phototoxic drug reaction in a patient with renal cell carcinoma.